Differential Subtypes of Offending Among Adolescent Girls Predict Health and Criminality in Adulthood. (February 2014) - Henneberger, Angela K.; Oudekerk, Barbara A.; Reppucci, N. Dickon; Odgers, Candice L.
This study tests whether subtyping justice-involved adolescent girls into violent and delinquent (VAD), delinquent only, and low subgroups is predictive of adult health and offending. We use data from the Gender and Aggression Project to examine young adulthood functioning among women ( N = 114) who were incarcerated during adolescence. After controlling for age, initial official-reports of offending, and baseline scores on the outcome of interest, the VAD subgroup experienced the worst functioning in young adulthood. Compared with the delinquency only subgroup, the VAD subgroup recidivated at higher rates and reported more internalizing psychopathology and physical health discomfort. Findings indicate that justice-involved girls should not be treated as a homogeneous group and prevention and intervention services should focus on girls who are most at risk in adolescence.